Development of Science Education Videos Based on Digital Storytelling as An Independent Learning Resource for Late Adolescents - Utami, Afifah Indra; Sauqina, Sauqina; Sari, Mella Mutika (Journal of Innovative Science Education, 2023)
The increasing interest of late adolescents in digital content provides an excellent opportunity to distribute self-learning resources that can facilitate understanding science concepts in daily life. Unfortunately, social media as a means of disseminating digital content is still dominated by entertainment content. The lack of science education videos that are interesting and suitable for the characteristics of late adolescents on social media causes late adolescents to prefer entertainment content over educational content. Therefore, this research was initiated to develop a science education video based on digital storytelling and identify aspects of validity, practicality, and effectiveness of educational videos as a source of independent learning for late adolescents. This research includes Research and Development (R&D), using the 4D model of defining, designing, developing, and disseminating. This research produced a product in the form of a science education video based on digital storytelling as an independent learning resource for late adolescents that has been declared valid, practical, and effective. The validation percentage score of 82.5% is included in the very valid category. The practicality aspect met the very practical criteria, with a score of 92.66%. Effectiveness received an N-Gain score of 0.78 and was included in the high category. Based on the study's results, this digital storytelling-based science education video can be utilized as an independent learning resource for late adolescents.